Determining effects of adolescent stress exposure on risk for posttraumatic stress disorder in adulthood. (December 2020) - Chaby, Lauren E; Lasseter, Heather C; Geier, Charles; Jeromin, Andreas
Highlights: Identifying biological signals of PTSD risk conferred by adolescent stress will facilitate diagnostic and therapeutic development. Putative biological signals can be evaluated by duration, additive effects, and disease state specificity. PTSD with/without childhood trauma may be distinguished by epigenetic patterns. Cortisol is unlikely to be a marker of adolescent stress that compounds risk for PTSD. Promising yet discordant findings for cytokines highlight the need for further study. Abstract : Clinical evidence indicates that stressful experiences during adolescence can increase rates of posttraumatic stress disorder (PTSD) in adulthood, while prospective evidence from animal models shows that stress in adolescence can increase risk or resilience to the effects of subsequent stress exposure. We discuss recent evidence of lasting effects from adolescent stress in clinical and rodent studies and leverage these findings to evaluate putative biological markers of PTSD etiology. To do this, we evaluate effects of stress in adolescence based on duration, interaction with subsequent stressors, and disease-specificity. We focus on biological systems suggested to integrate effects of developmental stress and distinguish PTSD from related disease states, including hypothalamic-pituitary-adrenal (HPA) axis function, inflammatory cytokine profiles, and epigenetic mechanisms. Our synthesis of recent literature highlights extensive variability in the design of rodent studies of adolescent stress, including stress timing, type, and duration. Given that windows of plasticity fluctuate throughout adolescence, these procedural differences pose challenges for integrating findings. We also find that the majority of recent studies find no lasting effects of adolescent stress on glucocorticoids stress responsivity, such that other biological markers of HPA function may be necessary to capture potential lasting effects of adolescent stress on HPA regulated stress response systems. Conversely, the breadth of early evidence for elevated cytokines highlights both the promise of this field and the challenges from incomplete characterization with respect to sex-differences and non-linear maturation during adolescence. Overall, efforts to map cross-species maturational trajectories, enhance replicability in preclinical findings, and characterize longitudinal trajectories following adolescent stress could facilitate the translation of findings from animal models to clinical contexts.